Cognition from genes to ecology: individual differences incognition and its potential role in a social network - Brian H. Smith (Animal Cognition)
Abstract There have now been many reports of intra-colony differences in how individuals learn on a variety of conditioning tasks in both honey bees and bumble bees. Yet the fundamental mechanistic and adaptive bases for this variation have yet to be fully described. This review summarizes a long series of investigations with the honey bee (Apis mellifera) that had the objective of describing the factors that contribute to this variation. Selection on haploid drones for extremes in learning performance revealed that genotype accounted for much of the variance. Neither age nor behavioral caste consistently accounted for observed variation on different conditioning protocols until genotype was controlled. Two subsequent Quantitative Trait Locus mapping studies identified a locus in the honey bee genome with a significant effect on the learning phenotype. Pharmacological and reverse genetic approaches, combined with neurophysiological analyses, confirmed that a biogenic amine receptor for tyramine affects expression of the trait. This work allowed for development of a hypothetical model of how that receptor functions in the brain to produce broad pleiotropic effects on behavior. Subsequent work used genotype as a treatment condition for evaluation of the variation under quasi-natural conditions, which revealed that individual variation reflects how foragers weigh known and novel resources in decision making. This work, together with other studies of individual differences, suggests a unifying framework for understanding how and why individuals differ in cognitive abilities.